Effects of 405-, 532-, 650-, and 940-nm wavelengths of low-level laser therapies on orthodontic tooth movement in rats - Hasibe Baser Keklikci; Ahmet Yagci; Arzu Hanim Yay; Ozge Goktepe (SpringerOpen, 2020)
Abstract Background Investigating the effects of 405-nm, 532-nm, 650-nm, and 950-nm wavelengths of LLLTs (low-level laser therapies) on the orthodontic tooth movement in rats by using histological and immunohistochemical methods. Forty-five Wistar albino rats were randomly divided into 5 groups: control group (positive control: the left maxillary 1st molar side; negative control: the right maxillary 1st molar side), 405 nm LLLT group (Realpoo), 532 nm LLLT group (Realpoo), 650 nm LLLT group (Realpoo), and 940 nm LLLT group (Biolase). The left maxillary 1st molar teeth of all rats were applied mesially 50-g force. Starting from the 1st day, 48 h intervals, LLLT was applied in continuous wave mode and in contact with the tissue. The application area was approximately 1 cm2. The lasers were performed for 3 min on each surface (buccal, palatal, mesial), totally 9 min (total dose 54 J/cm2). The amount of the molar mesialization, the bone area between the roots, PDL (periodontal ligament) measurements, TRAP (tartrate-resistant acid phosphatase), and ALP (alkaline phosphatase) immunoreactivity intensity were calculated. Results The amount of the molar mesialization was significantly higher in the 650 nm LLLT group (mean 0.878 ± 0.201 mm; 95% CI (confidence interval) 0.724 and 1.032) than in the groups of positive control (mean 0.467 ± 0.357 mm; 95% CI 0.192 and 0.741) and 405 nm LLLT (mean 0.644 ± 0.261 mm; 95% CI 0.443 and 0.845) (p < 0.001). There were significant differences in the PDL-mesial (p = 0.042) and PDL-distal (p = 0.007) regions between the groups. The immunoreactivity intensity for TRAP-mesial was significantly higher in the positive control group (mean 109,420.33 ± 8769.17; 95% CI 100,217.65 and 118,623.02) than in the 405 nm (mean 91,678.83 ± 7313.39; 95% CI 84,003.9 and 99,353.77) and the 650 nm LLLT (mean 87,169.17 ± 4934.65; 95% CI 81,990.56 and 92,347.77) groups (p = 0.002). There was no statistically significant difference between the groups on immunoreactivity intensity with ALP staining. Conclusions The results of this study show that LLLT with 650-nm wavelength increases orthodontic tooth movement more than 405-nm, 532-nm, and 940-nm LLLTs. The 940-nm and 650-nm LLLTs also increase the bone area between the roots by more than 405-nm and 532-nm wavelengths.